THE ANALYSIS OF GREBEG MULUD AS TOURISM POTENTIAL - YULIANA, TABITA PUTRI DEWI; ZANAH, SRI WAHYUNI SAMARATUL (RADIANT: Journal of Applied, Social, and Education Studies, 2020)
In this research the writer sees many kind of culture that can be potential tourism from the many unique points especially the culture tourism. It is meant it invites readers to be more interested in preserving the traditional culture.This research uses qualitative descriptive method. The research involves the data that consist of the primary and secondary sources. Qualitative modes of data analysis provide ways of discerning, examining, comparing and contrasting, and interpreting meaningful patterns or themes. Grebeg Mulud or Sekaten is a series of events in Javanese tradition that has special significance for the javanese people. Grebeg Mulud or Sekaten event has also become one of the history of the spread of Islam by Walisongo, which was first implemented in the Kingdom of Demak and then inherited by the Surakarta Palace. This event has great value, which then appealed to the tourists for just a look or even learn about the traditions and ultimately make them as one of the leading tourism circuit and attractions in Surakarta. Even in this modern and sophisticated area, the traditional events are still being kept by its people. It is proven that traditions still has the main role in people’s life and behavior.